Hepatitis E virus ORF 1 induces proliferative and functional T‐cell responses in patients with ongoing and resolved hepatitis E. (20th August 2017) - Al‐Ayoubi, Jana; Behrendt, Patrick; Bremer, Birgit; Suneetha, Pothakamuri Venkata; Gisa, Anett; Rinker, Franziska; Manns, Michael P.; Cornberg, Markus; Wedemeyer, Heiner; Kraft, Anke R. M.
Abstract: Background and Aims: Hepatitis E virus (HEV) is a major cause of acute viral hepatitis with >3 million symptomatic cases per year accounting for 70 000 HEV‐related deaths. HEV‐specific T‐cell responses have been investigated against structural proteins expressed by open reading frames (ORF) 2 and 3. T‐cell responses against non‐structural HEV proteins encoded by ORF1 are hardly studied. The aim of this study was to determine HEV ORF1‐specific T‐cell responses in comparison to ORF2/3 in patients exposed to HEV. Methods: HEV‐specific CD4 + and CD8 + T‐cell responses against HEV genotype 3 were investigated in patients with acute and chronic hepatitis E as well as in HEV seropositive and seronegative individuals. HEV‐specific T‐cell responses were determined by proliferation and intracellular cytokine assay upon stimulation of PBMCs with HEV‐specific overlapping peptide pools spanning the entire HEV genome. HEV‐antigen was measured using an anti‐HEV antigen‐specific ELISA. Results: Broad HEV ORF1‐specific T‐cell responses were detected in patients with acute, resolved and chronic hepatitis E without distinct dominant regions. The magnitude and frequency in recognition of ORF1‐specific T‐cell responses were similar compared to responses against HEV ORF2/3. Longitudinal studies of HEV‐specific T‐cell responses displayed similar behaviour against structural and non‐structural proteins. HEV‐antigen levels were inversely correlated with HEV‐specific T‐cell responses. Conclusions: HEV‐specific T‐cell responses are detectable against the entire HEV genome including the non‐structural proteins. HEV‐specific T‐cell responses are associated with control of HEV infection. These findings have implications for the design of HEV vaccines.